Scientific evidence and rationale for the development of curcumin and resveratrol as nutraceutricals for joint health - Mobasheri, Ali; Henrotin, Yves; Biesalski, Hans-Konrad; Shakibaei, Mehdi (MDPI, 2012)
Interleukin 1β (IL-1β) and tumor necrosis factor α (TNF-α) are key cytokines that drive the production of inflammatory mediators and matrix-degrading enzymes in osteoarthritis (OA). These proinflammatory cytokines bind to their respective cell surface receptors and activate inflammatory signaling pathways culminating with the activation of nuclear factor κB (NF-κB), a transcription factor that can be triggered by a host of stress-related stimuli including, excessive mechanical stress and ECM degradation products. Once activated, NF-κB regulates the expression of many cytokines, chemokines, adhesion molecules, inflammatory mediators, and several matrix-degrading enzymes. Therefore, proinflammatory cytokines, their cell surface receptors, NF-κB and downstream signaling pathways are therapeutic targets in OA. This paper critically reviews the recent literature and outlines the potential prophylactic properties of plant-derived phytochemicals such as curcumin and resveratrol for targeting NF-κB signaling and inflammation in OA to determine whether these phytochemicals can be used as functional foods.